ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN PADA SATUAN KERJA PERANGKAT DAERAH PEMERINTAH PROVINSI NTB TAHUN 2020-2022 - Astrid Wirawati; Siti Fatimah; Sujadi (Elastisitas : Jurnal Ekonomi Pembangunan, 2023)
This study aims to ascertain the impact of planning, procurement of goods and services, human resources, and utilization of information technology on budget absorption in the regional work units of the NTB Provincial Government in 2020-2022. The type of research conducted is quantitative research with an associative approach using primary data sources through the distribution of questionnaires to several respondents. The sampling technique used purposive sampling. The research sample was taken 6 respondents each in 6 work units with the largest APBD budget, so that in total there were 36 respondents. The analysis technique uses multiple linear regression analysis with the SPSS 16.0 statistical test tool. The results of research with multiple linear regression analysis show that partially the planning variable (X1) has a positive and significant effect on budget absorption (Y), while the variable procurement of goods and services (X2), human resources (X3), and utilization of information technology (X4) have no significant effect on budget absorption (Y). Simultaneously, the variables of planning, procurement of goods and services, human resources, and utilization of information technology have a significant effect on budget absorption.